The Effect of Teaching Strategies and Learning Styles on the Students™ Achievement (LINGUISTIK TERAPAN, 2014)
This research investigates 1) students™ achievement in reading comprehension taught by using Direct Reading Thinking Activity (DR-TA) strategy is higher than taught by using Know, What to Learn, and Learned (KWL) strategy, 2) students™ achievement in reading comprehension with impulsive learning style is higher than students™ achievement in reading comprehension with reflective learning style, and (3) there is  interaction between teaching strategies and learning styles on the students™ achievement. Two classes containing of 70 students were chosen as sample by apllying cluster random sampling technique. The experimental group 1 was treated by using DR-TA and the experimental group 2 was treated by using KWL. The students™ achievement was measured by using test. The questionnaire was conducted to find out the students™ learning style. The data were analyzed by applying two-ways analysis of variance. The findings show that (1) the students™ achievement in reading comprehension taught by using DR-TA higher than using KWL; (2) students™ achievement in reading comprehension with impulsive learning style is lower than that with reflective learning style; (3) there is interaction between teaching strategies and learning styles on the students™ achievement in reading comprehension. The analysis revealed that the teaching strategies significantly affected the students™ reading achievement.   Keywords: DR-TA, KWL, Impulsive Learning Style, Reflective Learning Style, Reading Comprehension